KAP study regarding ill effects of smoking over the health of people particularly oro-dental health and their prevention - Gul, Riaz; Zarif, Adil; Gul, Hira (Journal of Gandhara Medical and Dental Science, 2018)
ABSTRACTS The effects of smoking on human health are serious and in many cases, deadly. There are approximately 4000 chemicals in cigarettes, hundreds of which are toxic. The ingredients in cigarettes affect everything from the internal functioning of organs to the efficiency of the body’s immune system; the effects of cigarette smoking are destructive and widespread. All forms of tobacco including cigars, smokeless tobacco, and huka pose dental health concerns OBJECTIVES: To Assess the knowledge/awareness, attitude and practices (KAP) of people about adverse effects of smoking on their health particularly oro-dental health METHODOLOGY: The study was conducted in two teaching hospital of Peshawar i.e. KCD (Khyber college of dentistry and SBDC (Sardar begum dental college).it was a cross sectional descriptive study carried out over400 patients who attended the OPD of these hospitals for some reasons. Approval of the study was taken from the ethical committees of both the hospitals. Non probability sampling technique was adopted for the study. All relevant information about the study was gathered with the help of semi structured questionnaire. Purpose of the study was explained to the patients. The study was conducted from May 2016 to November 2016. Patients with systemic diseases that could affect oro-dental health were excluded from the study. Data was presented in the form of tables and graphs. RESULTS: According to their dentist 52% of study patients had adverse oral hygiene. About 74.5% smokers were aware of adverse effects of smoking. 55% of the people who smoke cigarette are 21-30 years of age. 26.5% people smoked 1-3 times a day. . In a significant number of patients 41% people started smoking because of peer pressure. Mass media had a significant role in developing this habit. About 74.5% are aware of adverse effects of smoking and they consider that it causes bad effects on respiratory system and oral hygiene. Most of the smokers use tooth paste to get rid of bad breath. About 59% people visited dentist only when some oro-dental problem arises. According to dentist 39.5% of smokers have adverse oral health status. CONCLUSION: Despite of knowledge of adverse effects of smoking and complaining of bad breath and other conditions related to oro-dental hygiene, majority of them were engaged in regular smoking and they are still satisfied from their oral health ,